Surgical treatment of a giant right atrial myxoma - Ryosuke Numaguchi; Makoto Hashimoto; Ryuji Koshima; Keijiro Mitsube (Surgical Case Reports)
Abstract Background Right atrial myxoma is a rare anomaly. When present, it can rarely cause blood flow obstruction in the right cardiac chamber depending on its size and location. We herein report a rare case of a giant right atrial myxoma, which caused right heart failure due to tricuspid valve obstruction, along with our treatment experience. Case presentation A 59-year-old woman was admitted to our hospital for palpitations and edema of the lower extremity. Computed tomography image and transthoracic echocardiography showed a 57 mm × 63 mm giant tumor obstructing the tricuspid valve inflow. The tumor was excised surgically and the residual septal defect was repaired with a Dacron patch. Tricuspid valve annuloplasty was performed additionally. The postoperative course was uneventful and the patient was discharged on postoperative day 5. Conclusion Giant right atrial myxoma is a rare cause of tricuspid valve stenosis and right heart failure. Surgical resection is the most appropriate treatment option and should be performed as soon as possible after diagnosis.